Environment as a limiting factor of the historical global spread of mungbean - Ong, Pei-Wen; Lin, Ya-Ping; Chen, Hung-Wei; Lo, Cheng-Yu; Burlyaeva, Marina; Noble, Thomas; Nair, Ramakrishnan Madhavan; Schafleitner, Roland; Vishnyakova, Margarita; Bishop-von-Wettberg, Eric; Samsonova, Maria; Nuzhdin, Sergey; et al. (eLife, 2023)
While the domestication process has been investigated in many crops, the detailed route of cultivation range expansion and factors governing this process received relatively little attention. Here, using mungbean ( Vigna radiata var. radiata ) as a test case, we investigated the genomes of more than 1000 accessions to illustrate climatic adaptation’s role in dictating the unique routes of cultivation range expansion. Despite the geographical proximity between South and Central Asia, genetic evidence suggests mungbean cultivation first spread from South Asia to Southeast, East and finally reached Central Asia. Combining evidence from demographic inference, climatic niche modeling, plant morphology, and records from ancient Chinese sources, we showed that the specific route was shaped by the unique combinations of climatic constraints and farmer practices across Asia, which imposed divergent selection favoring higher yield in the south but short-season and more drought-tolerant accessions in the north. Our results suggest that mungbean did not radiate from the domestication center as expected purely under human activity, but instead, the spread of mungbean cultivation is highly constrained by climatic adaptation, echoing the idea that human commensals are more difficult to spread through the south-north axis of continents. Mungbean, also known as green gram, is an important crop plant in China, India, the Philippines and many other countries across Asia. Archaeological evidence suggests that humans first cultivated mungbeans from wild relatives in India over 4,000 years ago. However, it remains unclear how cultivation has spread to other countries and whether human activity alone dictated the route of the cultivated mungbean’s expansion across Asia, or whether environmental factors, such as climate, also had an impact. To understand how a species of plant has evolved, researchers may collect specimens from the wild or from cultivated areas. Each group of plants of the same species they collect in a given location at a single point in time is known collectively as an accession. Ong et al. used a combination of genome sequencing, computational modelling and plant biology approaches to study more than 1,000 accessions of cultivated mungbean and trace the route of the crop’s expansion across Asia. The data support the archaeological evidence that mungbean cultivation first spread from South Asia to Southeast Asia, then spread northwards to East Asia and afterwards to Central Asia. Computational modelling of local climates and the physical characteristics of different mungbean accessions suggest that the availability of water in the local area likely influenced the route. Specifically, accessions from arid Central Asia were better adapted to drought conditions than accessions from wetter South Asia. However, these drought adaptations decreased the yield of the plants, which may explain why the more drought tolerant accessions have not been widely grown in wetter parts of Asia. This study shows that human activity has not solely dictated where mungbean has been cultivated. Instead, both human activity and the various adaptations accessions evolved in response to their local environments shaped the route the crop took across Asia. In the future these findings may help plant breeders to identify varieties of mungbean and other crops with drought tolerance and other potentially useful traits for agriculture.